Estresse docente : a espiral do conhecimento como base para estratégias de enfrentamento em escolas públicas ofertantes de educação profissional na cidade de Foz do Iguaçu (PR) - Fernandes, Fernando Roberto Varnier (2016)
In public brazillian's middle and high schools, the work of teachers is pervaded by increasing social and bureaucratic demands, forcing teachers face long working hours which frequently extends beyond school time. Work overload and poor structural resources are pointed as potentially stress-generating conditions faced by teachers who work in public schools. Among the inespecific sets of physiological, psychological and social symptoms characteristic to stress, the reduction of immunological response is a typical one, rendering teachers vulnerable to occupational diseases resulting from exposure to unhealthy conditions and agents (e.g., chalk powder, dust, mold, toner, noise, heat/cold) and from the efforts characteristic to the profession (e.g., intensive talking, repetitive movements, inappropriate posture sustained for long time). The resulting discomfort of such diseases makes them both a result and a source of stress, starting a cycle in which stress facilitates the emergence of diseases and the diseases generates higher stress levels. If sustained for long time, professional aid (e.g. medical/psychological) will be required to stop this cycle. If detected in its early stage, however, actions aimed to eliminate/mitigate stressors and/or to reestablish an individual's energy, called coping strategies, can be capable of stop the evolution to a pathological level of stress, preserving teacher's health and performance. Knowledge about the coping strategies, as well as knowledge about stress and its causes and consequences, is a common feature in the literature about coping strategies. That said, could knowledge creation and sharing mitigate the adverse effects of stress on teacher's health? This research aims to analyze potential relations between the knowledge creation and sharing approach called SECI Model (Socialization, Externalization, Combination, Internalization) and estimated stress levels of teachers working in five public middle and high schools in Foz do Iguaçu (Brazil) which offer technical education courses. This study uses qualitative research techniques (e.g., focal groups, direct observation and document analysis) to access contextual and experiential data about teacher's subjective experiences of stress. Such data will be used to support the development of a self-administered questionnaire which data will be used to estimate the stress levels of the respondents and reveal its eventual relations with attitudes related to the SECI model. The results show a positive relation between attitudes related to the SECI model and the participant's estimated stress levels, probably due to the prevalence of Socialization and Internalization processes without support of organizational Externalization and combination processes.